Modulation of Calcitonin, Parathyroid Hormone, and Thyroid Hormone Secretion by Electrical Stimulation of Sympathetic and Parasympathetic Nerves in Anesthetized Rats - Hotta, Harumi; Onda, Akiko; Suzuki, Harue; Milliken, Philip; Sridhar, Arun (Frontiers in Neuroscience, 2017)
The thyroid and parathyroid glands are dually innervated by sympathetic (cervical sympathetic trunk [CST]) and parasympathetic (superior laryngeal nerve [SLN]) nerve fibers. We examined the effects of electrical stimulation of efferent or afferent nerve fibers innervating the thyroid and parathyroid glands on the secretion of immunoreactive calcitonin (iCT), parathyroid hormone (iPTH), 3,3’,5-triiodothyronine (iT3), and thyroxine (iT4) from the thyroid and parathyroid glands. In anesthetized and artificially ventilated rats, thyroid venous blood was collected. The rate of hormone secretion from the glands was calculated from plasma hormone levels, measured by ELISA, and the flow rate of thyroid venous plasma. SLNs or CSTs were stimulated bilaterally with rectangular pulses with a 0.5-ms width. To define the role of unmyelinated nerve fibers (typically efferent), the cut peripheral segments were stimulated at various frequencies (up to 40 Hz) with a supramaximal intensity to excite all nerve fibers. The secretion of iCT, iT3, and iT4 increased during SLN stimulation and decreased during CST stimulation. iPTH secretion increased during CST stimulation, but was not affected by SLN stimulation. To examine the effects of selective stimulation of myelinated nerve fibers (typically afferent) in the SLN, intact SLNs were stimulated with a subthreshold intensity for unmyelinated nerve fibers. iCT, iT3, and iT4 secretion increased during stimulation of intact SLNs at 40 Hz. These results suggest that excitation of myelinated afferents induced by low intensity and high frequency stimulation of intact SLNs promotes secretion of CT and thyroid hormones from the thyroid gland, potentially via reflex activation of parasympathetic efferent nerve fibers in the SLN.